Influence of Electronic Money Transfer Services on Performance of Small and Medium Enterprises in Kenya (A CASE OF BUNGOMA COUNTY) - Akwanyi, Marvin; Mburu, Dr. David Kiarie (IJRDO - Journal of Applied Management Science, 2016)
According to the 2013 Economic Survey, the SME sector, contributed 18.4% of the country’sGross Domestic Product (GDP). This shows the importance of SMEs to the Kenyan economymainly as a source of employment to an ever increasing populationhe use of mobile bankingservices has continued to grow over time as aapplication of the mobile phones for mobilebanking has marked a new frontier in mobile phone technology with an ever increasingnumber of small and medium enterprises using it in their transactions to enhance theirperformance. The role of electronic money transfer services has been viewed as a criticalelement for the performance of small and medium-sized enterprises. Typically, smallerenterprises face higher transactions costs than larger enterprises in obtaining creditInsufficient funding has been made available to finance working capital for the SMEs (Poorefficiency and consumer convenience practices have hampered the ability of smaller andmedium enterprises and Entrepreneur ICT Competency such as Information asymmetriesassociated with lending to small scale borrowers have restricted the flow of finance tosmaller and medium enterprises. In spite of these claims however, some studies show a largenumber of small and medium enterprises fail because of perceived value of m-banking andtransaction costs due to poor record keeping and lack of basic business managementexperience and skills are major contributors to failure of small business. The number of usesto which mobile banking services can be put keeps increasing with time. Small and mediumenterprises in Kenya have adopted the use of the mobile payments as a way of transactingtheir business because of the relative affordability of mobile phones and the mobile bankingservices they offer. However, it is not clear how mobile banking service use influences theperformance of small and medium enterprises. The study sought to determine if its use inBungoma County, a rural setting, has resulted in improvement on performance of small andmedium enterprises. The study will be based on a survey of 3680 small and mediumenterprises, from three major sectors of the Kenyan economy, agriculture, service andprocessing sectors. Small and medium enterprises that will be studied are those that havebeen in existence for more than 5 years and have experienced business without mobilebanking services before 2008, and thereafter with it. The study was built on the theories ofdiffusion of innovation theory, technology acceptance model and Schumpeter’s theory. Themain purpose of this study is to establish influence of mobile banking services onperformance of small and medium enterprises in Kenya. The study was guided by thefollowing specific objectives: To find out the influence of mobile transfer services onperformance of small and medium enterprises in Kenya; To investigate the influence ofinternet banking services on performance of small and medium enterprises in Kenya; Toexamine the influence of access to finance on performance of small and medium enterprisesin Kenya; To study the influence of e-commerce on performance of small and mediumenterprises in Kenya and to establish the influence of perceived value m-banking onperformance of small and medium enterprises in Kenya The study adopted a descriptivesurvey and a stratified sampling technique method was used and data was collected throughthe use of questionnaires. The correlation and regression analysis was used to establish thedirection and strength of the relationship of the variables at 5% level of significance. Theanalysis showed that access to finance services had the strongest positive (Pearsoncorrelation coefficient =.852) performance of SMEs. In addition, mobile banking services,internet banking services and e-commerce services were positively correlated to performance